Evaluación de cuatro estrategias químicas para el control del Psílido de la Papa (bactericera cockerelli) en sus diferentes estadios del Cultivo de Papa (solanum tuberosum) en la variedad Súper Chola en la Provincia de Cotopaxi, Cantón Salcedo, Parroquia Cusubamba - Barrio Compañía Baja. - Aguayza Mangui, Holger Arturo (2020)
AbstractThe present investigation gas carried out in the province of Cotopaxi, Salcedo cantón, Cusubamba parish, Compañía Baja neighborhood, with the objective of evaluating chemical strategies to control the insect vector that is affecting the potato crop. Different strategies were used, 18 active ingredients including insecticides and pesticides were used to perform an adequate control of the psilid of the potato. It was applied a completely randomized block design (DBCA) with four repetitions and four treatments obtaining a total of 16 experimental units. With the implementation of the design it was established the trial of super chola potato cultivation at a density of 0.30 centimeters between plants and 1.49 meters between rows, each experimental unit was delimited with 6.5 meters wide and 9.8 meters long with a separation of 1 meter between treatments, each treatment conformed of 147 plants. Giving a density of 2,352 plants in the entire area of the test. The application of active ingredients was carried out with 15-day rotations from week 6 to week 20. The cost for each treatment was made considering the unit value of the active ingredients and the cost produced per quintal. The yield for each treatment was considered by the number of quintals produced and related to tons per hectare.